GRAND MOSQUE OF AL-MASHUN: HISTORY, ARCHITECTURE, AND RELATIONSHIP WITH DOMED MOSQUES IN EAST SUMATRA RESIDENCY - KEMALASARI (NIM: 25215010), JEUMPA
Mosques that are built generally have a general elements, but still have dissimiliar characteristics. These characteristics are usually carried out by the socio-cultural conditions of the local community. Martin Frisman ever wrote that the peculiarities of mosques in the Southeast Asia region are using stacked roof construction, as well as in Indonesia. But at the beginning of the 20th century Grand Mosque of Al-Mashun was built using a dome roof. This raises questions about why Grand Mosque of Al-Mashun is different from other mosques. This question became one of many factors to study about Grand Mosque of Al-Mashun. In addition, there are still rare for people to study about this Mosque. So there are still a lot of information that is not known yet, such as who is the architect of Grand Mosque of Al-Mashun and how the buildings are being developed. However, after further study, not only the Grand Mosque of Al-Mashun uses a dome roof. Seven other mosques use the dome roof as well, namely Al-Osmani Mosque, Baiturrahman Mosque, Azizi Mosque, Binjai Grand Mosque, Stabat Grand Mosque, Penyengat Grand Mosque, and Syahabuddin Mosque. The entire mosque is located on the island of Sumatra, but five mosque are located nearby, namely Al-Osmani Mosque, Azizi Mosque, Binjai Grand Mosque, Stabat Grand Mosque, and Grand Mosque of Al-Mashun. Interestingly, the religion has similarities, like the shape of a dome. To abridge the study, in this study only five mosques were observed. The mosques are located in the residency of East Sumatra, which is now better known as the province of North Sumatra. The main focus of this research is to discuss the history and architecture of the Grand Mosque of Al-Mashun. Al-Osmani Mosque, Azizi Mosque, Binjai Grand Mosque, and Stabat Grand Mosque discussed briefly to see if there was a connection between the mosque and the Grand Mosque of Al-Mashun. The aim of this research is to describe the characteristics and history of the physical development of Grand Mosque of Al-Mashun, and to examine the relationship between Grand Mosque of Al-Mashun and other domed mosques in the East Sumatra Residency. Data collection was carried out with field surveys, stakeholder interviews, collecting literature, and old photographs. From the results of the discussion found several findings. The first finding is Th. van Erp as the architect of the Grand Mosque of Al-Mashun. The second finding is nothing change with physical of Grand Mosque of Al-Mashun. The last finding basic on Architectural analysis found that there is a relationship between the other domed mosque and Grand Mosque of Al-Mashun. Grand Mosque of Al-Mashun is the latest development of the other four mosques.